2012
DOI: 10.1124/mol.112.080838
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Kalirin-7 Knockout Mice Reveals Different Effects in Female Mice

Abstract: Estradiol treatment of ovariectomized rodents is known to affect the morphology of dendritic spines and produce behavioral and cognitive effects. Kalirin-7 (Kal7), a postsynaptic density (PSD)-localized Rho-guanine nucleotide exchange factor, is important for dendritic spine formation and stability. Male Kal7 knockout [Kal7(KO)] mice exhibit a number of abnormal behavioral and biochemical phenotypes. Given that chronic 17␤-estradiol (E2) replacement of ovariectomized rats enhanced Kal7 expression in the hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 58 publications
(102 reference statements)
0
30
0
Order By: Relevance
“…Behavioral studies of mice lacking Kal7 (Kal7 KO ) revealed its essential role in fear-based learning and in the response to chronic cocaine 13-16 . KalSR KO (full Kalirin knockout) mice show similar behavioral and drug-dependent deficits in addition to endocrine, cardiac and skeletal deficiencies 1 7-19 .…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral studies of mice lacking Kal7 (Kal7 KO ) revealed its essential role in fear-based learning and in the response to chronic cocaine 13-16 . KalSR KO (full Kalirin knockout) mice show similar behavioral and drug-dependent deficits in addition to endocrine, cardiac and skeletal deficiencies 1 7-19 .…”
Section: Introductionmentioning
confidence: 99%
“…While some of these abnormalities are shared with Kal7 KO mice, others are not (Kiraly et al 2010;Kiraly et al 2013;Lemtiri-Chlieh et al 2011;Ma et al 2008;Mazzone et al 2012); shared traits, such as the decrease in anxiety-like behavior and impaired contextual fear learning, may reflect the loss of Kal7. Since several of the traits exhibited by KalSR KO mice involve aberrant pituitary hormone secretion and several behavioral phenotypes suggest hypothalamic-pituitary-adrenal involvement, we chose to test the effects of eliminating Kalirin expression only in cells which express POMC at some time during development or in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…4). Several of the deficits identified in Kalirin knockout mice are also sex-specific (Mandela et al 2012;Mazzone et al 2012). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations